2012
DOI: 10.1080/15325024.2011.616832
|View full text |Cite
|
Sign up to set email alerts
|

Early Interventions Following Exposure to Traumatic Events: Implications for Practice From Recent Research

Abstract: It is has been argued that early interventions for individuals, groups or others affected by traumatic events should not be routinely offered as there is the danger of causing more harm. The notion of ''watchful waiting'' has been espoused in clinical guidelines for the assessment and treatment of posttraumatic stress disorder (PTSD). Instead, a more proactive early intervention is suggested for potentially traumatic events that have the potential to lead to high psychic distress, PTSD, or complicated grief re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 38 publications
1
28
0
1
Order By: Relevance
“…[151][152][153] These studies reinforce hippocampal research demonstrating that lesions to the Hip in the first 30 days after a negative event will eliminate the memory of the event, but lesions applied after the 30 days will fail to eliminate the memory, suggesting that traumatic memories are transferred from the Hip to long-term storage in other cortical sites (the mPFC, ACC, and IC) after 30 days. 154 Early psychological intervention has shown lower PTSD symptoms with psychiatric and counseling intervention in the emergency room 155 and progressive care after hospitalization.…”
Section: Fear and Pain Extinctionsupporting
confidence: 73%
“…[151][152][153] These studies reinforce hippocampal research demonstrating that lesions to the Hip in the first 30 days after a negative event will eliminate the memory of the event, but lesions applied after the 30 days will fail to eliminate the memory, suggesting that traumatic memories are transferred from the Hip to long-term storage in other cortical sites (the mPFC, ACC, and IC) after 30 days. 154 Early psychological intervention has shown lower PTSD symptoms with psychiatric and counseling intervention in the emergency room 155 and progressive care after hospitalization.…”
Section: Fear and Pain Extinctionsupporting
confidence: 73%
“…Received wisdom suggests that early intervention should be better than delayed intervention. However, there is now some evidence that if the intervention is too early, it may disrupt natural healing processes in adults (e.g., Dyregrov & Regel, 2012; Mayou, Ehlers, & Hobbs, 2000) and appears ineffective in preventing persistent PTSD symptoms when used with children (e.g., Stallard et al, 2006; Zehnder, Meuli, & Landolt, 2010). In contrast to single session early interventions for all trauma-exposed children, a screen-and-intervene approach in which a more intense multi-session early intervention is provided for symptomatic children appears promising (Berkowitz, Stover, & Marans, 2011).…”
Section: The Situation In 2012mentioning
confidence: 99%
“…A review of literature on intervention programs revealed that engaging survivors in distracting or enjoyable activities, the presence of caring helpers, and adequate provision of information promotes calm, reduces anxiety, and promotes recovery (Dryregrov & Regel, 2012). Given robust evidence on the protective role of social support, Dryregrov and Regel (2012) also advocate for the provision of 'structured social support' .…”
Section: Mental Health and Psychosocial Support During Emergenciesmentioning
confidence: 99%
“…Rather than wait for the onset of PTSD, Dryregrov and Regel (2012) suggest the need for early interventions to help survivors correct maladaptive thoughts and behaviours that may have enduring impact. The past years have seen an increasing number of MHPSS interventions designed to help survivors experiencing difficulties postdisaster.…”
mentioning
confidence: 99%